2017
DOI: 10.1158/1078-0432.ccr-16-0355
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of Large-Cell Neuroendocrine Carcinoma of the Lung

Abstract: Purpose: Although large-cell neuroendocrine carcinoma (LCNEC) of the lung shares many clinical characteristics with small-cell lung cancer (SCLC), little is known about its molecular features. We analyzed lung LCNECs to identify biologically relevant genomic alterations.Experimental Design: We performed targeted capture sequencing of all the coding exons of 244 cancer-related genes on 78 LCNEC samples [65 surgically resected cases, including 10 LCNECs combined with non-small cell lung cancer (NSCLC) types anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 40 publications
6
103
2
Order By: Relevance
“…However, further studies that take these variables into account need to be undertaken. Regarding combined LCNEC, Miyoshi et al also performed targeted NGS in 10 cases of combined LCNEC, and found that the median concordance rate of candidate somatic mutations between the two components was 71 % [11]. Interestingly, five of 10 cases of LCNEC combined with NSCLC harbored driver gene alterations, all of which were shared between the two components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further studies that take these variables into account need to be undertaken. Regarding combined LCNEC, Miyoshi et al also performed targeted NGS in 10 cases of combined LCNEC, and found that the median concordance rate of candidate somatic mutations between the two components was 71 % [11]. Interestingly, five of 10 cases of LCNEC combined with NSCLC harbored driver gene alterations, all of which were shared between the two components.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, it is very common for LCNEC to occur in combination with components of other lung cancers, such as SCLC, adenocarcinoma, and squamous cell carcinoma [11]. The failure to consider any of the individual components during pathological diagnosis may result in the choice of a systemic therapy that allows resistance and recurrence to develop [12].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other cancers, particularly breast and NSCLC, the use of ‘omics’ to identify subgroups in SCLC is in its infancy. Several whole exome sequencing (WES) studies and one whole genome sequencing (WGS) study on SCLC [ 14 , 15 , 20 - 22 ] are beginning to provide insight into the biology of this disease. Subgroup stratification in SCLC is hindered, however, by the wide heterogeneity and low frequency ( < 10%) of most genes mutated in SCLC beyond the two which define this cancer, TP53 and RB1 .…”
Section: Discussionmentioning
confidence: 99%
“…PTEN mutations and/or loss are detected in 4–9% of human SCLC and LCNEC (6, 36, 43, 44). Loss of PTEN expression in 55% of murine SCLC despite expression in precursor lesions suggests that PTEN loss promotes SCLC progression (28, 29).…”
Section: Discussionmentioning
confidence: 99%